2021
DOI: 10.1016/j.paid.2020.110350
|View full text |Cite
|
Sign up to set email alerts
|

All the Dark Triad and some of the Big Five traits are visible in the face

Abstract: Some of the recent studies suggested that people can make accurate inferences about the level of the Big Five and the Dark Triad personality traits in strangers by only looking at their faces. However, later findings provided only partial support and the evidence is mixed regarding which traits can be accurately inferred from faces. In the current research, to provide further evidence on whether the Big Five and the Dark Triad traits are visible in the face, we report three studies, two of which were preregist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…This works particularly well with the factors conscientiousness and extraversion (Little and Perrett, 2007). Another recent study (Alper et al, 2021) showed that agreeableness and conscientiousness are correctly inferred, while extraversion is correctly inferred in women. For our study, we chose prototypical faces for all Big Five factors (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness).…”
Section: The Present Studymentioning
confidence: 53%
See 1 more Smart Citation
“…This works particularly well with the factors conscientiousness and extraversion (Little and Perrett, 2007). Another recent study (Alper et al, 2021) showed that agreeableness and conscientiousness are correctly inferred, while extraversion is correctly inferred in women. For our study, we chose prototypical faces for all Big Five factors (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness).…”
Section: The Present Studymentioning
confidence: 53%
“…Trust in individuals with extreme levels of these traits can be particularly risky, as they are often selfish and manipulative. In studies with prototypical composite faces, it was shown that people can recognize the personality traits of the Dark Triad in people only by their faces (Holtzman, 2011;Alper et al, 2021).…”
Section: The Present Studymentioning
confidence: 99%
“…A growing number of studies have linked facial images to personality. It has been established that humans are able to perceive certain personality traits from each other's faces with some degree of accuracy [3] [4] [5][6] [7]. In addition to emotional expressions and other nonverbal behaviors that convey information about a person's psychological processes through the face, research has found that valid inferences about personality characteristics can even be made based on static images of faces with neutral expressions [8][9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…We can draw at least four valid inferences from other people's facial features [7]. Reference [8] examined the relationship between self-reported personality traits and first impressions. To investigate whether a computer can learn to assess human traits, the authors of [9] used a machine learning method to construct automatic feature predictors based on facial structure and appearance descriptors and found that all personality traits analyzed were accurate predictors.…”
Section: Introductionmentioning
confidence: 99%